UNFAIR TERMINATION OF EMPLOYMENT AT WORKPLACES - Madinda, Alexander S. (International Journal of Emerging Trends in Science and Technology, 2014)
In the 18th to the 19th century, the world stated to experience major changes in the means of productions, changes in agriculture, mining, transportation, manufacturing and technology. These changes made a major turning point in human history, as they had effects on the social, economic and cultural perspective of that time. It is industrial revolution that resulted into a need for countries to create effective national system of labor administration to improve employees’ rights, working condition, and productivity for sustainable development. In ensuring employees rights are not infringed this paper therefore seeks to identify the grounds for unfair termination of employment at work places. It starts with the introduction then reviewing theories and practical experience of different cases that happened in Tanzania under unfair dismissal grounds. The application of Tanzania Employment & Labor Relations Act (2004) in regard to unfair dismissal was also cited by this paper so as to enhance the relevancy of the findings and recommendations made. The paper goes on discussing the notice and remedies for termination of employment and identifying problems that lead to unfair procedures of termination of employee’s employment at workplaces and recommend measures on how to combat the problem. The paper ends up by a conclusion.